H2SO4 + Na2CO3 = Na2SO4 + CO2↑ + H2O
2H(+) + SO4(2-) + 2Na(+) + CO3(2-) = 2Na(+) + SO4(2-) + CO2↑ + H2O
2H(+) + CO3(2-) = CO2↑ + H2O
H2SO4 + 2KOH = K2SO4 + 2H2O
2H(+) + SO4(2-) + 2K(+) + 2OH(-) = 2K(+) + SO4(2-) + 2H2O
H(+) + OH(-) = H2O
H2SO4 + MgO = MgSO4 + H2O
2H(+) + SO4(2-) + MgO = Mg(2+) + SO4(2-) + H2O
2H(+) + MgO = Mg(2+) + H2O
H2SO4 + Fe = FeSO4 + H2
2H(+) +2e = H2(0) 1 в-ие
ок-ль
Fe(0) -2e = Fe(+2) 1 ок-ие
в-ль
H2SO4 + Zn(OH)2 = ZnSO4 + 2H2O
2H(+) + SO4(2-) + Zn(OH)2 = Zn(2+) + SO4(2-) + 2H2O
2H(+) + Zn(OH)2 = Zn(2+) + 2H2O
Объяснение:
Объяснение:
H2SO4 + Na2CO3 = Na2SO4 + CO2↑ + H2O
2H(+) + SO4(2-) + 2Na(+) + CO3(2-) = 2Na(+) + SO4(2-) + CO2↑ + H2O
2H(+) + CO3(2-) = CO2↑ + H2O
H2SO4 + 2KOH = K2SO4 + 2H2O
2H(+) + SO4(2-) + 2K(+) + 2OH(-) = 2K(+) + SO4(2-) + 2H2O
H(+) + OH(-) = H2O
H2SO4 + MgO = MgSO4 + H2O
2H(+) + SO4(2-) + MgO = Mg(2+) + SO4(2-) + H2O
2H(+) + MgO = Mg(2+) + H2O
H2SO4 + Fe = FeSO4 + H2
2H(+) +2e = H2(0) 1 в-ие
ок-ль
Fe(0) -2e = Fe(+2) 1 ок-ие
в-ль
H2SO4 + Zn(OH)2 = ZnSO4 + 2H2O
2H(+) + SO4(2-) + Zn(OH)2 = Zn(2+) + SO4(2-) + 2H2O
2H(+) + Zn(OH)2 = Zn(2+) + 2H2O
1.Zn
+HCL=ZnCl{2}[/tex]+H2O
n(Zn(OH)2)=m/M=99/99=1 Моль
1/1=1/x
n(H2O)=1 *1/1=1 моль
m(H2O)=n*M=18г